Keeping reptiles as pets in Brazil: keepers' motivations and husbandry practices - María Fernanda De la Fuente; Bruna Monielly Carvalho de Araújo; Iamara da Silva Policarpo; Heliene Mota Pereira; Anna Karolina Martins Borges; Washington Luiz Silva Vieira; Gentil Alves Pereira Filho; Rômulo Romeu Nóbrega Alves (BMC, 2023)
Abstract Background Reptiles are considered one of the most popular pets in the world and are often associated with an incorrect belief that they are simple, highly adaptable, and easy to keep animals when compared with other pets, such as dogs and cats. However, keeping reptiles as pets can pose several challenges in meeting their needs in a domestic setting, requiring specific conditions and effort to maintain their health, well-being, and survival. Methods During 2015, using online semi-structured questionnaires applied to 719 Brazilian pet reptile keepers who participated in online groups of reptile breeders on the social network Facebook, this study aimed to identify Brazilian keepers' motivations for maintaining reptiles as pets, investigate their monthly expenses, and the husbandry practices for the maintenance, such as housing and feeding conditions, handling of the animal, health issues, and treatment provided. Results We found multiple motivations for keeping reptiles as pets (mostly snakes, lizards, and chelonians), the main motivation being emotional reasons, followed by entertainment and convenience reasons. The great majority of keepers (69%) declared to spend less than or up to US$30 per month in maintaining their reptiles. Most reptiles were kept alone in terrarium/aquarium enclosures, with basic environmental complexity in terms of physical elements. Lizards and chelonians were fed with a few insect species, cultivated fruits and vegetables, while snakes were fed mainly with domestic rodents, rabbits, or birds. Keepers declared frequent cleaning of the enclosure, but inappropriately handled their animals directly with their hands, which might result in potential threats to human and reptile health and safety. Several diseases or injuries were mentioned and 55.6% of the keepers declared taking the reptile to the vet for treatment. Conclusions Overall, our findings revealed several challenges that reptiles face when kept in domestic environments, including issues related to housing, nutrition, and healthcare. Even though keepers demonstrated positive feelings toward their pets, suggesting a positive relationship and a willingness to provide them with proper care, it seems that without the proper knowledge and awareness, reptiles may unintentionally be kept with poor husbandry. Addressing these challenges on husbandry practices is essential for improving reptiles' welfare and promoting a responsible pet ownership.